2006
DOI: 10.1111/j.1600-0765.2006.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of lipid peroxides and antioxidants in smokers and nonsmokers

Abstract: The study results show that smoking increases the level of free radicals in periodontal tissues, which in turn may be responsible for the destruction seen in periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
42
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 25 publications
(18 reference statements)
19
42
3
1
Order By: Relevance
“…Smoking is associated with altered expression and activity of antioxidant enzymes. According to the studies [32,33] cigarette smoking is associated with a significant decrease in the level of SOD, however some other studies [34,35] have documented that compared to non smoker controls the bidi smokers have shown increased erythrocyte SOD activity. We have observed a relatively higher SOD Values are mean ± SD * P values are obtained using one way analysis of variance (ANOVA) with Tukey's correction for multiple group comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with altered expression and activity of antioxidant enzymes. According to the studies [32,33] cigarette smoking is associated with a significant decrease in the level of SOD, however some other studies [34,35] have documented that compared to non smoker controls the bidi smokers have shown increased erythrocyte SOD activity. We have observed a relatively higher SOD Values are mean ± SD * P values are obtained using one way analysis of variance (ANOVA) with Tukey's correction for multiple group comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction between pathogenic bacteria and the host immune response is accompanied by an increase in cytokine expression and immunological activity in gingival tissues (13). Thus, large amounts of pro-oxidants are produced in prolonged inflammatory response, as seen in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Garg et al [18] observed the delicate balance between ROS and tissue concentrations of antioxidants may be disturbed by various factors including smoking. Elevated levels of ROS stimulate neutrophils to upregulate the adhesion integrins, leading to their increased accumulation in tissues and a local sealing off of antioxidant enzymes, such as SOD, catalyse and protease inhibitors, as observed by Ryder et al [19].…”
Section: Discussionmentioning
confidence: 99%